GHD diagnostics in Europe and the US: an audit of national guidelines and practice - Binder, Gerhard; Reinehr, Thomas; Ibáñez, Lourdes; Thiele, Susanne; Linglart, Agnès; Woelfle, Joachim; Saenger, Paul; Bettendorf, Markus; Zachurzok, Agnieszka; Gohlke, Bettina; Randell, Tabitha; Hauffa, Berthold P.; et al. (Hormone research in paediatrics, 2019)
Almost 20 years after the first international guidelines on the diagnosis and treatment of GHD have been published, clinical practice varies significantly. The low accuracy of endocrine tests for GHD and the burden caused by ineffective treatment of individual patients were strong motives for national endocrine societies to set up national guidelines regarding how to diagnose GHD in childhood. This audit aims to review the current state and identify common changes, which may improve the diagnostic procedure.